Effectiveness of Endorphine Massage Technique on Labor Pain in Mothers in The Active Phase of First-Stage Labor at PMB Siti Aisyah, Amd.Keb, Bogor Regency - Muliani, Rima; Nurasiah, Siti (Westscience Press, 2025)
Normal childbirth is a natural process that occurs in a woman. During the birthing process, complications are very likely to occur which can endanger both the mother and the baby and are one of the causes of maternal death. This study aims to determine the effectiveness of Endorphine Massage on labor pain in mothers in the first stage of active labor at PMB Siti Aisyah, Amd.Keb, Bogor Regency.The research method used is quasi-experimental with a Two-group pre and posttest design. The sample was taken using a total sampling technique of 20 respondents. The instrument in this study used the Endorphine Massage Standard Operating Procedure (SOP) sheet and the Numeric Rating Scale (NRS) consisting of a scale of 0-10 to describe the intensity of pain experienced by respondents. The results of the study showed that there was a significant difference in the pain scores of respondents before and after being given Endorphine Massage with a paired simple t-test obtained a p-value = 0.000. Endorphin massage technique is effective in reducing pain in mothers giving birth during the first active phase at PMB Siti Aisyah, Amd.Keb, Bogor Regency